2017
DOI: 10.1186/s13690-017-0190-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing risky single occasion drinking in Canada and policy implications

Abstract: BackgroundMisuse of alcohol, including single risky occasion drinking (RSOD) is associated with a number of health, social and economic consequences. While research demonstrates that many factors contribute to individuals’ drinking practices, little is known about risk factors that contribute to RSOD in the Canadian population. The objectives of this study are to examine the patterns of RSOD in Canada, to identify factors associated with RSOD, and to explore policy implications.MethodsThe Canadian Community He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 43 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…The education factor significantly influences the culture of palm wine consumption in Bumi Wali Tuban. Rafferty, Ellen, in the results of the study stated that, individuals with less education than secondary school had a 1.09 times higher chance than individuals with education after secondary school (14) . Anamaria Ciubară's research also states that the level of education also influences general attitudes toward alcoholism and alcoholism, subjects with higher education are far more aware of the negative effects of alcoholism than subjects with less educational levels (15) .Low education factor makes it difficult for someone to accept new information, in this case is information about wine and its effects, even though they argue that drinking wine is a negative habit.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The education factor significantly influences the culture of palm wine consumption in Bumi Wali Tuban. Rafferty, Ellen, in the results of the study stated that, individuals with less education than secondary school had a 1.09 times higher chance than individuals with education after secondary school (14) . Anamaria Ciubară's research also states that the level of education also influences general attitudes toward alcoholism and alcoholism, subjects with higher education are far more aware of the negative effects of alcoholism than subjects with less educational levels (15) .Low education factor makes it difficult for someone to accept new information, in this case is information about wine and its effects, even though they argue that drinking wine is a negative habit.…”
Section: Discussionmentioning
confidence: 90%
“…Rafferty, Ellen, in her study said that, as individual income levels increase, the estimated opportunities for engaging in alcohol consumption also increase. Individuals with higher incomes tend to drink more often than low income earners (14) . Sobhee's research, S, also states that spending to buy alcohol by alcohol dependent individuals increases when income rises.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of more than 16,000 military personnel, stress was positively associated with heavy alcohol in the past month among men [ 22 ]. A study conducted in Canada, based on the CCHS 2010, reported that perceived stress increased the odds of infrequent Risky Single Occasion Drinking (RSOD) but not frequent RSOD [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Canada found a range of variables affecting alcohol consumption. For example, a study based on 2009/2010 Canadian Community Health Survey (CCHS) data indicated significant differentials in alcohol consumption by gender, marital status, residence, cigarette smoking, income, education, and perceived health status [ 9 ]. The Public Health Agency of Canada reported a range of factors influencing high alcohol consumption, including alcohol access and affordability, gender norms, social environment “(e.g., social and cultural practices, loss of cultural identity, stigma, social networks, and supports),” socio-economic position, occupation type, individual motivations for drinking, coping abilities and lack of knowledge about the risks [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation